2019
DOI: 10.1126/scirobotics.aau7897
|View full text |Cite
|
Sign up to set email alerts
|

Robots mediating interactions between animals for interspecies collective behaviors

Abstract: Self-organized collective behavior has been analyzed in diverse types of gregarious animals. Such collective intelligence emerges from the synergy between individuals, which behave at their own time and spatial scales and without global rules. Recently, robots have been developed to collaborate with animal groups in the pursuit of better understanding their decision-making processes. These biohybrid systems make cooperative relationships between artificial systems and animals possible, which can yield new capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 69 publications
1
42
0
Order By: Relevance
“…Thus, in some sense, these robots need to exert control over their organismic counterparts. We identified that social interaction might be one of the key factors here, as social systems tend to be self-organising systems where modest modulation of a few actors (Halloy et al, 2007;Bonnet et al, 2018) or of some small-scale local environment (Bonnet et al, 2019) can already change the collective local densities, which is known to be a fundamental factor in ecological interactions: It is a longestablished fact that systems like predator-prey systems (Lotka, 1925;Volterra, 1926), host-parasite systems (Anderson and May, 1978), epidemic spread dynamics (Kermack and McKendrick, 1927), intra-specific competition (Verhulst, 1845), and interspecific competition (Smale, 1976) are strongly driven by local population densities, not only affecting population dynamics but also relevant for their future configuration through natural selection (Hardin, 1960). In short, there is no ecologically relevant interaction amongst organisms that is not affected by the local density distributions of organisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in some sense, these robots need to exert control over their organismic counterparts. We identified that social interaction might be one of the key factors here, as social systems tend to be self-organising systems where modest modulation of a few actors (Halloy et al, 2007;Bonnet et al, 2018) or of some small-scale local environment (Bonnet et al, 2019) can already change the collective local densities, which is known to be a fundamental factor in ecological interactions: It is a longestablished fact that systems like predator-prey systems (Lotka, 1925;Volterra, 1926), host-parasite systems (Anderson and May, 1978), epidemic spread dynamics (Kermack and McKendrick, 1927), intra-specific competition (Verhulst, 1845), and interspecific competition (Smale, 1976) are strongly driven by local population densities, not only affecting population dynamics but also relevant for their future configuration through natural selection (Hardin, 1960). In short, there is no ecologically relevant interaction amongst organisms that is not affected by the local density distributions of organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish used in the studies here was approved by the state ethical board for animal experiments under authorisation number 2778 from the DCVA of Canton de Vaud, Switzerland. As described in Bonnet et al (2019) , we used 100 wild-type, short-fin zebrafish ( Danio rerio Hamilton 1822) with average length of 4 cm, sourced from Qualipet (Crissier, Switzerland). Each fish could be used in a maximum of one experiment per day, and all fish used were returned to their main tank at the end of the day, meaning that the same individuals could appear in multiple replicates of the studies presented here.…”
Section: Towards a Proactive Contingency: Organismic Augmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our concept of behavioral teleporting is related to two recent, independent breakthroughs by Bonnet and collaborators ( Bonnet et al., 2019 ) and Larsch and Baier ( Larsch and Baier, 2018 ). Bonnet and collaborators demonstrated the feasibility of remote interaction between zebrafish and honeybees in binary decision-making tasks through biologically-inspired robots (a zebrafish replica and two bee-robots).…”
Section: Introductionmentioning
confidence: 99%
“…Larsch and Baier demonstrated the possibility of establishing remote social interactions between zebrafish within a virtual reality setup, wherein projected dots instantaneously replicated the motion of independent subjects located in different tanks. Our approach combines these two strategies by affording the transfer of the complete ethogram of a zebrafish, similar to Larsch and Baier (2018) , onto a three-dimensional robotic replica, similar to Bonnet et al. (2019) .…”
Section: Introductionmentioning
confidence: 99%